Extraosseous calcifying odontogenic cyst: a case report and a literature review - Cazal,Claudia (2005)
The calcifying odontogenic cyst is an uncommon odontogenic lesion that can have intra- or extraosseous occurrence with both cystic or tumor behavior. A report of an extraosseous calcifying odontogenic cyst (ECOC) in a 57-year-old black woman is presented as well as a review of the literature about the lesion. The clinical, radiographic and histopathologic features are discussed, along with etiology and treatment.